2012
DOI: 10.1148/radiol.12112458
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Myocardial Fibrosis Assessed as Extracellular Volume Fraction with Low-Radiation-Dose Cardiac CT

Abstract: Purpose:To develop a cardiac computed tomographic (CT) method with which to determine extracellular volume (ECV) fraction, with cardiac magnetic resonance (MR) imaging as the reference standard. Materials and Methods:Study participants provided written informed consent to participate in this institutional review board-approved study. ECV was measured in healthy subjects and patients with heart failure by using cardiac CT and cardiac MR imaging. Paired Student t test, linear regression analysis, and Pearson cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
113
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(134 citation statements)
references
References 31 publications
8
113
0
1
Order By: Relevance
“…Through the dual-energy technique, measurements were only performed on the iodine maps of equilibrium contrast-enhanced cardiac CT, which resulted in accurate measurements of ECV with minimal misregistration. In one study, investigators reported a bias of 23.01%, with 95% limits of agreement from 22.82% to 8.85% for ECV measurement between MR imaging and CT (11). Another study demonstrated a bias of 1.40% but with wide 95% limits of agreement (234.70% to 31.90%) (12).…”
Section: Baseline Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the dual-energy technique, measurements were only performed on the iodine maps of equilibrium contrast-enhanced cardiac CT, which resulted in accurate measurements of ECV with minimal misregistration. In one study, investigators reported a bias of 23.01%, with 95% limits of agreement from 22.82% to 8.85% for ECV measurement between MR imaging and CT (11). Another study demonstrated a bias of 1.40% but with wide 95% limits of agreement (234.70% to 31.90%) (12).…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…Although a few studies about myocardial ECV on cardiac CT images have been published (11)(12)(13)(14), a method involving both unenhanced (precontrast) and contrast-enhanced (postcontrast) CT is thought to be of limited use, because the myocardium and blood might not be easily differentiated on precontrast CT images, and misregistration between the pre-and postcontrast CT images might reduce accuracy.…”
Section: Study Populationmentioning
confidence: 99%
“…Whilst CCT has been used to accurately demonstrate ventricular myocardial fibrosis 115,116 CMR remains the accepted standard. 117 Improvements in CMR techniques in recent years have allowed them to be applied to thin-walled structures such as the LA.…”
Section: Scar Formationmentioning
confidence: 99%
“…An experimental ECVF calculation equation has been proposed in our previous work, 10 but the principle behind the ECVF calculation has not been elucidated so far. In this section, we present the derivation of the ECVF calculation equation based on the tissue compartmental model.…”
Section: A Principle Of Ecvf Calculation Using Dual-phase Ct Imagesmentioning
confidence: 99%
“…Therefore, we sought to use a dual-phase cardiac CT to determine ECVF and demonstrated the successful substitution of cardiac CT for cardiac MR in ECVF analysis in our previous work. 10 However, the low contrast sensitivity and poor quality of the low dose CT images pose a significant challenge in integrating this novel technique into the clinic practice.…”
Section: Introductionmentioning
confidence: 99%